Analysis of human papillomavirus prevalence and TP53 polymorphism in head and neck squamous cell carcinomas - Cortezzi, S. S.; Provazzi, P. J.; Sobrinho, J. S.; Mann-Prado, J. C.; Reis, PMP; de Freitas, SEN; Gois, J. F.; Fukuyama, E. E.; Cordeiro, J. A.; Cury, P. M.; Maniglia, J. V.; Villa, L. L.; et al. (Elsevier B.V., 2004)
Head and neck squamous cell carcinoma is a disease associated with tobacco and alcohol abuse. There is evidence that the oncogenic human papillomavirus (HPV) may also be a risk for upper aerodigestive tract cancers. High-risk HPVs encode two early proteins, E6 and E7, that can bind to p53 and pRb, respectively, and induce its degradation or inactivation. The TP53 gene has a single polymorphism at codon 72 of exon 4 that encodes either arginine (Arg) or proline (Pro). The purpose of this study was to evaluate the role of HPV infection and TP53 polymorphism in head and neck cancer. We analyzed 50 tumors, as well swabs of oral mucosa front 142 control individuals, with a polymerase chain reaction technique. The prevalence of HPV in controls was 10.6% and in cancer specimens 16%. The frequency distribution of genotypes in controls was 50% Arg/Arg, 43% Arg/ Pro and 7% Pro/Pro; in tumors, it was 52% Arg/Arg, 32% Arg/Pro, and 16% Pro/Pro. Contrary to the results of some studies on cervical cancer, no association between any TP53 genotype or allele and the development of head and neck cancer was observed, regardless of HPV status, except for the Pro/Pro genotype, which is associated with the absence of HPV. The arginine allele appears to protect against head and neck cancers. Also, the data showed that HPV infection results in no increased risk of developing head and neck tumors. (C) 2004 Elsevier B.V. All rights reserved.